Prostate cancer transfection by acoustic energy using pEGFP-N1 as reporter gene in the solid Dunning R-3327-MatLu tumor - Michel, Maurice Stephan; Erben, Philipp; Trojan, Lutz; Knoll, Thomas; Alken, Peter (Prostate cancer and prostatic diseases, 2003)
Background: Gene therapy is expected to play a major role in medical treatment in the future. Several different methods for DNA transfection exist. We evaluated the efficacy and effects of transfection by acoustic energy in a standardized prostate cancer model.